Examen Especial a los bienes de larga duración de la Dirección Distrital 11D09 Zapotillo-Salud durante el periodo 2016 - Moncayo Navarrete, Angel Medardo (2018)
The present work called: "Special Examination of Long-Term Assets of the District Office 11D09 Zapotillo-Salud during the 2016 period" was developed based on the provisions of the Academic Regulations to meet a prerequisite to qualify for the Degree of Engineer in Accounting and Auditing, Public Accountant Auditor at the National University of Loja. Its main purpose is to carry out a Special Examination of the Long-Term Assets of District Office 11D09 Zapotillo-Salud during the 2016 period, in order to verify the management and control of the component examined for the efficient provision of services to citizens. Next, the Internal Control System was evaluated in the planning, to assess compliance with the processes of the Long Term Assets of District Directorate 11D09 Zapotillo-Salud. Check the reasonableness of the balances of the Long Term Assets found in the respective Financial Statements, presented by the institution in the period under review. Subsequently, the Audit procedures were executed to determine the reasonableness of the balances and the procedures for derecognition and balance updating, which was executed applying the Internal Control Standards and the legal and regulatory provisions subject to the Public Sector through the Internal Control Questionnaire. , applying the phases of Audit: Planning, Execution and Communication of Results, with the purpose of contributing with results aimed at issuing an opinion. Finalizing with the 5 issuance of the report containing Comments, Conclusions and Recommendations through communication of results aimed at making decisions where the audit report of the results obtained in the Special Exam is recorded, concluding that the entity does not make physical findings This makes it difficult to reconcile the physical balances with the accounting records, and assets that have reached their useful life have not been written off.